COMBINATION OF INVASIVE ASPERGILLOSIS AND MUCORMYCOSIS IN ONCOHEMATOLOGICAL PATIENTS - O. V. Shadrivova; S. N. Khostelidi; Yu. V. Borzova; E. A. Desyatik; A. G. Volkova; M. O. Popova; O. S. Uspenskaya; O. S. Ruzhinskaya; T. V. Shneyder; T. S. Bogomolova; S. M. Ignatyeva; L. S. Zubarovskaya; et al. (Онкогематология)
Objective. Data analysis of the register of patients with invasive aspergillosis (IA), which was founded in Saint Petersburg (1998–2017), and clinical case description of successful treatment of IA and mucormycosis with lungs involvement in a patient with Hodgkin’s lymphoma.Materials and methods. In the study were included 29 oncohematological patients with IA and mucormycosis. In control group were included 483 oncohematological patients with IA. We used criteria EORTS/MSG, 2008 for IA and mucormycosis diagnosis.Results. We identified that the combination of IA and mucormycosis significantly often develops in patients with acute lymphoblastic leukemia (32 %, р = 0.001), and allogeneic hematopoietic stem cells transplants (allo-HSCT) recipients (52 %, р = 0.001). In mixed-infection Aspergillus nidulans was frequent IA etiological agent (11 %, р = 0.001). The main mucormycosis etiological agents were Rhizopus spp. (45 %), Lichtheimia corуmbifera (20 %). The main sites of the localization were lungs (76 %), disseminated process and paranasal sinuses involvement were identified more frequently (45 % and 17 % (р = 0.0001; р = 0.002), respectively). Typical clinical feature of IA and mucormycosis combinations was hemoptysis (24 %, р = 0.008), radiological signs – lesions with cavities destruction (38 %), hydrothorax (29 %) and a “reverse halo” symptom (17 %). Antifungal therapy received 76 % of patients, surgery – 34 %.Conclusion. Mucormycosis was revealed in 5.7 % of patients with IA. The main risk factors for co-infection are allo-HSCT, long-term agranulocytosis, lymphocytopenia and glucocorticosteroid therapy. Overall 12 weeks survival in patients with mixed-infection was 38 %, significantly lower than in patients with IA (р = 0.005). An unfavorable prognosis factor was dissemination of mycotic infection (р = 0.009).